Internalization of Magelang' Local Wisdom in STEM Learning: Analysis of Pottery Making as a Science Learning Resource - Eli Trisnowati; Wiyanto; Bambang Subali; Sulhadi (Jurnal Penelitian Pendidikan IPA, 2023)
The context in science learning needs to be linked contextually and be interdisciplinary so that learning becomes more meaningful. This research aims to analyze the local wisdom of the people of Magelang Regency in making pottery as a science learning resource containing STEM (Science, Technology, Engineering and Mathematics) on temperature and heat. The subjects of this study were pottery artisans in Kragilan, Donorojo, Mertoyudan, Magelang, Central Java. The research design used is descriptive qualitative with data collection techniques in literature and field studies (interviews and documentation). The data in the research is qualitative, namely the results of interviews and identification of local wisdom in making pottery in Magelang Regency, which can be used as a science learning resource with STEM content. In addition, qualitative data analyses local wisdom in making pottery in science learning resources with STEM content on science material. This research shows that local wisdom in making Magelang pottery, especially roof tiles and braziers, is appropriate to the science learning context. The process of making pottery can be internalized in science learning as a science learning resource containing STEM (Science, Technology, Engineering, and Mathematics) for teaching Temperature and Heat material.